Efek Depresi terhadap Efektivitas Pengobatan Penyakit Crohn - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Milna Sari (Jurnal Ventilator, 2024)
Crohn's disease is a chronic inflammatory condition of the gastrointestinal tract that is often accompanied by psychological disorders such as depression. This study aims to analyze the impact of depression on the effectiveness of Crohn's disease treatment through a systematic review and meta-analysis. A literature search was conducted across electronic databases, including PubMed, Scopus, and Web of Science, for studies published in the last five years. Of the 1,247 articles identified, 28 studies met the inclusion criteria. The meta-analysis results indicate that Crohn's disease patients with depression have a lower remission rate (OR = 0.65, 95% CI: 0.54-0.78) and a higher relapse rate (HR = 1.58, 95% CI: 1.32-1.89) compared to patients without depression. Additionally, subgroup analysis reveals that the negative effects of depression are more pronounced in patients receiving biological therapy. These findings underscore the importance of a holistic approach in the management of Crohn's disease, considering the psychological aspects of patients to optimize treatment outcomes.